Secretome analysis of Ashbya gossypii - Aguiar, Tatiana Quinta (2010)
To explore the potential Ashbya gossypii extracellular secretome two computational protocols were used. The 4726 protein-encoding genes predicted in the genome of A. gossypii strain ATCC 10895 were the data source for the analysis. Depending on the computational methods used, 171 to 185 proteins were predicted to be secreted proteins. Based on the results of the present study, A. gossypii is more similar to the closely related yeast Saccharomyces cerevisiae than to other filamentous fungi in its secretion ability.